THE PERIOD OF NATIONAL AWAKENING IN UZBEK POETRY ECHO OF THE TREASURE VOICE OF THE NATION” - Djokhongirovna, Kholikova Nodira (International Journal of Psychosocial Rehabilitation, 2020)
As literature became increasingly close to social life, the content changed, while retaining the form of traditional genres in labor poetry; divine and romantic motives were replaced by socio-political motives, symbolic images were replaced by the image of a real person. The ideological-emotional image, which reflects the aesthetic ideals of the artists associated with national liberation, created a realistic pathos. Poetry dedicated to the events of labor reflected the social problems of the time, the secret thoughts of the nation, as well as pain and hatred, irony and anger, which raised the subjective feeling of the poet to the level of pathos